Effectiveness and Safety of a Fixed-Dose Combination of Valsartan and Rosuvastatin (Rovatitan® Tablet) in Patients with Concomitant Hypertension and Hyperlipidemia: An Observational Study - Lee KJ; Ryu JK; Cho YH; Shin WY; Kim JS; Yoon YW; Jang JY; Kim WH; Beom JW; Kang SM (Dove Medical Press, 2023)
Kwang Je Lee,1 Jae-Kean Ryu,2 Yun-Hyeong Cho,3 Won Yong Shin,4 Jeong Su Kim,5 Young Won Yoon,6 Ji Yong Jang,7 Won Ho Kim,8 Jong Wook Beom,9 Seok-Min Kang10 On behalf of LG-VROS001 STUDY INVESTIGATOR GROUP1Department of Internal Medicine, Chung-Ang University Hospital, Seoul, Korea; 2Department of Internal Medicine, Daegu Catholic University Medical Center, Daegu, Korea; 3Cardiovascular Center, Myongji Hospital, Goyang, Korea; 4Department of Cardiology, Soon Chun Hyang University Hospital Cheonan, Cheonan, Korea; 5Cardiovascular Center, Pusan National University Yangsan Hospital, Yangsan, Korea; 6Department of Internal Medicine, Gangnam Severance Hospital, Yonsei University College of Medicine, Seoul, Korea; 7Department of Cardiology, National Health Insurance Service Ilsan Hospital, Ilsan, Korea; 8Eulji University School of Medicine, Daejeon, Korea; 9Department of Cardiology, Jeju National University Hospital, Jeju, Korea; 10Severance Cardiovascular Hospital, Yonsei University College of Medicine, Seoul, KoreaCorrespondence: Seok-Min Kang, Division of Cardiology, Severance Cardiovascular Hospital, Yonsei University College of Medicine, Seoul, Korea, Tel +82 2-2647-3225, Email SMKANG@yuhs.acPurpose: This study aimed to assess the effectiveness and safety of a fixed-dose combination of rosuvastatin and valsartan (Rovatitan®) in Korean patients with concomitant hypertension and hyperlipidemia.Patients and Methods: A total of 1008 eligible patients with concomitant hypertension and hyperlipidemia were enrolled and treated for 12 weeks. Both upward and downward drug dose titrations were allowed based on the investigator's discretion. This study evaluated the effectiveness of the study drug, defined by the percentage of patients achieving the blood pressure (BP) and low-density lipoprotein cholesterol (LDL-C) treatment targets. Additionally, regression analyses were conducted to evaluate the factors associated with the effectiveness and safety of the study drug. Of the 1008 patients enrolled in the study, 911 were analyzed for clinical effectiveness.Results: At 12 weeks, 84.6% and 75.9% of patients treated with the study drug achieved their BP and LDL-C targets, respectively, and 64.8% of patients achieved both targets simultaneously. Furthermore, the percentage of patients who achieved their BP and LDL-C treatment targets demonstrated a trend across the respective risk groups; the higher the risk group, the lower the success of attaining the respective target. This trend was also observed regardless of the prior antihypertensive and/or lipid-lowering treatments. According to regression analysis, poor metabolic profiles, including a higher body mass index (BMI) and higher BP and LDL-C levels at baseline, were significantly associated with treatment failure for BP. Among the 1005 patients included in the safety analysis, 17 patients (1.7%) experienced serious adverse events; however, none were considered related to the study drug.Conclusion: The study drug used for the treatment of concomitant hypertension and hyperlipidemia in a real-world setting was effective and was well tolerated. Therefore, the study drug is suggested as a good alternative to increase patient convenience and compliance, particularly in those taking multiple medications.Keywords: hypertension, hyperlipidemia, rosuvastatin, valsartan, effectiveness, safety